SMS communication - Croatian SMS language features as compared with those in German and English speaking countries - Filipan, Blaženka (Revija za elementarno izobraževanje, 2012)
SMS is a relatively new asynchronous communication form, generally accepted in Croatia, where the number of mobile phones surpasses the number of the inhabitants. A language analysis of the corpus of SMS messages has been done for the purpose of this investigation, with the aim to examine the type of communication involved, and to establish whether the language in the Croatian SMS messages differs from those in German and English. It has been found that the limit of 160 characters in a single message presents a basic determining factor of the SMS discourse, as it requires utmost economy of the language used, i.e. briefness (saving the effort, space, time and money). The language analysis performed has also shown that SMS messages are used to communicate almost any topic of everyday life, as well as that, apart from numerous elements of deviation from the accepted language standards, they exhibit a lot of abbreviations, together with graphostylistic signs (emoticons) and Anglicisms. The language used in Croatian SMS messages does not differ significantly from that used in English or German messages of the same type.
Keywords: SMS discourse; SMS-sporočila; conceptually oral expression; jezikovne kode; grafični znaki; abbreviating; komunikacija; anglicisms; skrajšave; angleški izrazi; Croatia; Hrvaška